'A life I can cope with'. An alternative model of cognitive behavioural therapy (CBT) for CFS/ME - Dr. Catherine Clark; Dr. Sue Holttum (Wiley, 2022)
Abstract Objectives This study aimed to explore the experience of cognitive behavioural therapy (CBT) aimed at better management of chronic fatigue syndrome/myalgic encephalomyelitis (CFS/ME), rather than increasing activity. Design This was a qualitative study using grounded theory analysis. Methods Semi‐structured interviews were conducted with 13 adults who had engaged in CBT at a specialist CFS/ME service in which CBT is aimed at improved management of the condition. Results A model was produced in which participants felt more able to cope with CFS/ME. Reduced fatigue did not seem to be a necessary precondition to managing. This has implications for CBT for CFS/ME. Conclusions Specialist CBT for CFS/ME may result in improved coping and reduced distress, independently of changes in fatigue. Patient or Public Contribution The researcher met with a representative from the university's service user advisory group (SAGE), who had lived experience of CFS/ME. They commented on possible questions for the interview topic guide and provided advice on ways in which ethical issues specific to CFS/ME could be considered, for example, prevention of harm during interviews. Second, for quality assurance as part of respondent validation, a proposed draft of the grounded theory was discussed with participants.